The effect of age and unilateral leg immobilisation for 2 weeks on substrate ulilisation during moderate-intensity exercise in human skeletal muscle - Vigelsø, A.; Gram, M.; Dybboe, R.; Kuhlman, A.B.; Prats, C.; Greenhaff, Paul L.; Constantin-Teodosiu, Dumitru; Birk, J.B.; Wojtaszewski, J.F.P.; Dela, F.; Helge, J.W. (Wiley, 2016)
Age and inactivity have been associated with intramuscular triglyceride (IMTG) accumulation. Here, we attempt to disentangle these factors by studying the effect of 2 weeks of unilateral leg immobilization on substrate utilization across the legs during moderate-intensity exercise in young (n = 17; 23 ± 1 years old) and older men (n = 15; 68 ± 1 years old), while the contralateral leg served as the control. After immobilization, the participants performed two-legged isolated knee-extensor exercise at 20±1W(_50% maximalwork capacity) for 45 min with catheters inserted in the brachial artery and both femoral veins.Biopsy samples obtained from vastus lateralis muscles of both legs before and after exercise were used for analysis of substrates, protein content and enzyme activities. During exercise, leg substrate utilization (respiratoryquotient) did not differ between groups or legs. Leg fatty acid uptake was greater in older than in young men, and although young men demonstrated net leg glycerol release during exercise, older men showed net glycerol uptake. At baseline, IMTG, muscle pyruvate dehydrogenase complex activity and the protein content of adipose triglyceride lipase, acetyl-CoA carboxylase 2 and AMP-activated protein kinase (AMPK)γ3 were higher in young than in older men. Furthermore, adipose triglyceride lipase, plasma membrane-associated fatty acid binding protein and AMPKγ3 subunit protein contents were lower and IMTG was higher in the immobilized than the contralateral leg in young and older men. Thus, immobilization and age did not affect substrate choice (respiratory quotient) during moderate exercise, but the whole-leg and molecular differences in fatty acid mobilization could explain the age- and immobilization-induced IMTG accumulation.